Photoelectric effect accelerated electrochemical corrosion and nanoimprint processes on gallium arsenide wafers - Guo, Chengxin (Chem Sci, 2019)
Here we report photoelectric-effect-enhanced interfacial charge transfer reactions. The electrochemical corrosion rate of n-type gallium arsenide (n-GaAs) induced by the contact potential at platinum (Pt) and GaAs boundaries can be accelerated by the photoelectric effect of n-GaAs. When a GaAs wafer is illuminated with a xenon light source, the electrons in the valence band of GaAs will be excited to the conduction band and then move to the Pt boundaries due to the different work functions of the two materials. This results in an enhanced contact electric field as well as an enlarged Pt/GaAs contact potential. Consequently, in the presence of electrolyte solution, the polarizations of both the Pt/solution interface and the GaAs/solution interface at the Pt/GaAs/solution 3-phase boundary are enhanced. If the accumulated electrons on the Pt side are removed by electron acceptors in the solution, anodic corrosion of GaAs will be accelerated strictly along the Pt/GaAs/solution 3-phase boundary. This photo-enhanced electrochemical phenomenon can increase the corrosion rate of GaAs and accelerate the process of electrochemical nanoimprint lithography (ECNL) on GaAs. The method opens an innovative, highly efficient, low-cost nanoimprint technique performed directly on semiconductors, and it has prospective applications in the semiconductor industry.